The Effect of Giving Lemongrass Aromatherapy Oil and Love Lactation Massage on Breast Milk Production for PostPartum Mothers at Ciomas Health Center - Utami Subagio, Sri; ., Nurseha; Sundary Lintang, Santi (KnE Social Sciences, 2023)
The percentage of exclusive breastfeeding for infants 0-6 months in Banten province in 2019 was 64.4% in line with analysis data on stunting measurements in Ciomas subdistrict of 9.23%, which increased compared to 2020 which was 4.60%. Exclusive breastfeeding is an indicator of program coverage related to stunting that needs attention because the coverage of exclusive breastfeeding is only 31.56%. Seeing the milk production of post partum mothers who were given complementary therapies of love lactation massage and lemongrass aromatherapy. With a descriptive research design and a case study approach, the research samples were 2 postpartum mothers who were examined using an instrument using a questionnaire sheet on the adequacy of breast milk production before and after giving love lactation massage and lemongrass essential oil. Postpartum mothers who have low milk production after being given love lactation massage and lemongrass essential oil for 2 weeks with massage every morning experienced an increase in breast milk production based on 6 aspects that have been assessed, namely based on the mother’s condition about the condition of breast milk production and the condition of the baby who has been breastfed. There is an effect of giving love lactation massage and lemongrass essential oil for 4 weeks on the adequacy of breast milk. It is hoped that health workers can recommend love lactating massage and lemongrass essential oil aromatherapy to increase breast milk production in postpartum mothers. Keywords: love lactation massage and lemongrass essential oil, post partum mothers, breast milk production